Fungi with potential probiotic properties isolated from Fuzhuan brick tea - Xin Wang; Yuanyuan Cui; Chaowei Sang; Bin Wang; Yirong Yuan; Lin Liu; Yahong Yuan; Tianli Yue (Food Science and Human Wellness)
Several of the fungal species associated with Fuzhuan brick tea (FBT) are considered as potential probiotics, but few studies have investigated the probiotic properties of these fungi. Here, we isolated 18 fungal strains from two types of FBT and identified these strains based on internal transcribed spacer (ITS) fragment sequence similarity to reference strains (sequence similarity > 98%). Of the 18 strains, 10 tolerated simulated human digestive conditions for sufficient periods in vitro: pH 2-3, 0.3%-0.5% (m/V) bile salts, and artificial gastrointestinal juices. We then measured the antimicrobial activity of the remaining 10 strains against 5 enteropathogenic bacteria and tested the bacteriostatic effects of the thalli and fermentation broth extracts. Of the 6 strains with strong bacteriostatic effects, we eliminated Eurotium cristatum S-9 due to its low hydrophobicity of (26.12 ± 0.35)%. Finally, 2 exhibited good adhesion abilities to human cells (> 100%). Notably, 2 strains can survive in vivo, because they can be isolated from C57BL/6 mice feces. Thus, 2 strains, Aspergillus cristatus H-1 and A. cristatus H-5, are herein identified as promising candidate probiotic strains. It may be put forward a novel research focus on evaluating potential probiotic fungi from FBT.